Importer dynamics: Do peers matter? - Gregory Corcos; Stefanie Haller (University College Dublin, UCD School of Economics, 2023)
Few firms import, even when formal trade barriers are low and despite substantial potential gains. Likely reasons are uncertainty and informational frictions, creating scope for local peers to affect new importers. We explore this hypothesis using data on French imports by firm-product-country-year, location, and importer characteristics. First, we study the decision to start importing as a function of the lagged number of importers in the same commuting zone (CZ). We find that the presence of such peers more than doubles the probability to start importing the same product from the same country. The effect increases disproportionately with the number of peers. Second, we examine how the elimination of Multi-Fibre Agreement textile and clothing quotas affects the number of import starters at the CZ level. Here the number of import starters from quota countries increases by 40 to 90% more in commuting zones with a higher initial number of peers.
Keywords: 330